Efektivitas Quantity Take-Off dalam Proyek Swakelola dengan Integrasi Building Information Modeling (BIM) - Rizki, Alvan; Atik Wahyuni; Hendri Hermawan (AGREGAT, 2025)
The Quantity Take-Off (QTO) process plays a vital role in preparing construction cost estimates. However, conven-tional methods, which are still widely used in Indonesia particularly in self-managed projects often result in vol-ume deviations and require longer processing time. This study investigates the application of Building Information Modeling (BIM) using Autodesk Revit for QTO in the construction of an eight-story hospital project carried out through self-management. A quantitative experimental method was employed by comparing the QTO results of concrete and reinforcement in major structural elements from both approaches. The findings indicate that the av-erage deviation for concrete volume was 1.21%, while the average deviation for steel reinforcement was 1.75%. The highest concrete deviation occurred in shear walls (3.70%) due to differences in volume calculation for open-ings and elevation variations, whereas the highest reinforcement deviations were found in columns (2.72%) and beams (2.63%) as the conventional approach tends to simplify reinforcement details such as lengths, splices, and bends. The study concludes that BIM-based QTO is not only technically more reliable but also addresses the limita-tions of human resources in self-managed projects. Therefore, adopting BIM is strongly recommended as a digital transformation strategy for more efficient quantity management in infrastructure projects in Indonesia.